Changes In Local Government Management In The Implementation Of Electronic Governance - Ichsan Sudarsono, Faizaldi; Hayu Dwimawanti, Ida; Fauziah, Luluk (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The development of information and communication technology has encouraged changes in local government management by implementing electronic governance. The implementation of electronic governance has various benefits, including increasing transparency, accountability, efficiency, and public participation in the government decision-making process, as well as accelerating the resolution of public problems. This study aims to determine changes in local government management in implementing electronic governance. This type of research is qualitative research, while data collection techniques are carried out by literature study. The results showed that changes in local government management that can occur in the implementation of electronic governance include changes in the way local government works, interaction between local government and society, quality of public services, supervision and evaluation, decision making, data and information management and overall changes. Overall changes, the implementation of e-governance can bring significant changes in local government management, such as increased efficiency and effectiveness, more active community participation, better quality of public services, and more integrated data and information management